Concentric Bracing Frame in Earthquake-Resistant High-Rise Buildings - Alhussein, Mohammedalameen Ahmed Aldaw; Nugroho, Guntur; Wahiddin, Wahiddin; Nursetiawan, Nursetiawan (Universitas Muhammadiyah Yogyakarta, 2024)
Indonesia has regular earthquakes; thus, constructions must be designed to SNI 1726:2019. Building height based on SNI 1726:2012 table 9 and article 7.2.5.4 maximums. The survey says response-based damage models can assess ground vibrations. The earthquake damage was assessed and compared to the moment-resisting frame after the structure was rehabilitated with concentric bracing. 1) This study analyzes lateral forces on each level for moment-resisting and concentric-braced frames. CBF, 2) assessing displacements at each level for moment-resisting and concentric braced frames, and 3) counting narratives. The ETABS Structural Analysis Professional 2020 program measures structural element internal forces. Internal forces include shear, axial, bending, and twisting. Next, calculate level displacement, or vertical distance between levels. The pushover analysis on medium and high-rise structures shows 0.91% CBF lateral shear force. CBF stiffens elastically. CBF supports enhance CBF displacement by 70%, minimize floor structure displacement, and stiffen the steel frame laterally more than MRF. Maximum CBF deviation between floors is 85%; CBF and MRF weight differential is 1.530%. Thus, the CBF exceeds the frame weight. The designed structure is important, but seismic performance in static and dynamic nonlinear circumstances differs.